Quality planting material of pomegranate pays - Singh, N V; Chandra, Ram; Meshram, D T; Maity, Ashis; Pal, R K (Indian Horticulture, 2015)
Pomegranate cultivation ensures one of the highest returns on investment among most of the fruits crops grown under arid and semi-arid regions of India. The pomegranate cultivation in India is rapidly increasing at the rate of few thousand ha in 1990s to 112.2 lakh ha in 2012. In view of this rapid growth there is a huge demand of disease-free quality planting material. Establishment ofconventional and high tech nurseries will go a long way in meeting this huge demand of quality planting material and ensure huge entrepreneurial opportunity for educated youths in these areas.